EFFECT OF SYMMETRIC MOBILIZATION EXERCISES APPLIED SAGITTALE PLANE ON SPINE FLEXIBILITY AND ANGLE OF TRUNK ROTATION IN SCOLIOSIS - (:unkn) unknown (TURKEY ASSOC PHYSIOTHERAPISTS, 2015)
Purpose: Thoracic and lumber flatback has been assumed to be the triggerring factor for idiopathic scoliosis. It is belived that rotation and lateral deviation are secondary patterns of deformity in the development of idiopathic scoliosis, and it should be possible to improve scoliosis by forces in sagittal plane. It is suggested that Physio-logic (R) exercises stabilize the spine posture and correct scoliosis in 3-D. The aim of this study was to assess the effect of symmetric mobilization exercise which was defined in Physio-logic (R) exercises on spine flexibility and angle of trunk rotation. Methods: Thirty four patients (30 female, 4 male) with adolescent idiopathic scoliosis (AIS) were included in this study. King classification was used to classify of scoliosis types. Symmetric mobilization exercise was done 20 repetitions, 15 sessions in supin position under physiotherapist supervision. Spine flexibility was evaluated with forward and lateral bending test and angle of trunk rotation was measured with scoliometer. Evaluations were performed before and after every session. Results: The mean age of patients was 13.5years (range; 10-17). The mean Cobb angle was 31.64 degrees (range; 12 degrees-60 degrees) and angle of trunk rotation was 9.86 degrees (range; 3 degrees-16 degrees). Statistically significant improvements were observed for all assessed measurements after the treatment (p<0.05). Discussion: Our results showed that spine flexibility can be improved and angle of trunk rotation can be decreased by sagittal forces. Increasing of spine flexibility and decreasing angle of trunk rotation may prevent progression of scoliosis. We suggest that symmetric mobilisation exercises should take place in the rehabilitation programme of AIS.
Keywords: Scoliosis; Rehabilitation; Exercise Therapy; Joint Flexibility; Rotation; ADOLESCENT IDIOPATHIC SCOLIOSIS